(+1) - (-6)
wHEN I WAS IN 7TH GRADE I LEARNED A TRICK FROM REWRITING A SUBTRACTION PROBLEM... TWO SWIPES OF THE PEN
SWIPE 1: CHANGE THE MINUS SIGN TO AN ADDITION SIGN (PUT A LINE THROUGH THE MINUS SIGN AND IT BECOMES A PLUS SIGN):
(+1) + (-6)
sWIPE 2: CHANGE THE SIGN OF THE NUMBER AFTER THE SUBTRATION SIGN TO ITS OPPOSITE. THE OPPOSITE OF (-6) IS +6 (PUT A LINE THROUGH THE NEGATIVE SIGN AND IT BECOMES A POSITIVE SIGN):
(+1) + (+6)
sTEP 3: FINISH THE ADDITION:
1 + 6 = 7
nEXT QUESTION:
(-24) - (-32)=
oNCE AGAIN TWO SWIPES OF THE PEN:
SWIPE ONE: CHANGE THE MINUS SIGN TO AN ADDITION SIGN:
(-24) + (-32)=
SWIPE 2: CHANGE THE SIGN OF THE NUMBER AFTER THE SUBTRACTION SIGN. -32 BECOMES +32
(-24) + (+32)=
sTEP 3 REWRITE IT SO U SEE ITS A SIMPLE SUBTRACTION:
-24 + 32 IS THE SAME AS:
32 - 24
YOU KNOW 32 - 24 = 8
LAST PROBLEM:
(+2) - (-4)=
SWIPE 1 OF THE PEN: CHANGE THE SUBTRACTION SIGN TO AN ADDITION SIGN:
(+2) + (-4) =
SWIPE 2: CHANGE THE SIGN OF THE NUMBER AFTER THE MINUS SIGN. -4 BECOMES +4
(+2) + (+4) =
sTEP 3: FOLLOW THE RULES OF ADDITION:
(+2) + (+4) = 6
BIGGEST THING TO REMEMBER!!!!!!!!!!!!!!!
PLEASEEEEEEEEEEEEEEEEEEE USE THE FOLLOWING RULES CAREFULLY...
TWO POSITIVES = POSITIVE ANSWER
TWO NEGATIVES = POSTIVE ANSWER
ONE NEGATIVE AND ONE POSITIVE = NEGATIVE
HOW TO USE THESE RULES IN ADDITION AND SUBTRACTION ARE DIFFERENT THAN IN MULTIPLICATION AND STUDENTS TEND TO MIX UP THE DIFFERENCE. IF YOU ARE CONFIDENT YOU WONT CONFUSE THE DIFFERENCE THAT IS FINE. I JUST CAUTION YOU THAT MANY DO. IN ADDITION AND SUBTRACTION THE - - MUST BE DIRECTLY SIDE BY SIDE... I WOULDNT WANT YOU TO THINK -1 + -7 = 8.... TWO NEGATIVES IS A POSITIVE MAKES IT SEEM THAT ANSWER IS TRUE WHEN ITS NOT. tHE PERSON WHO USED THOSE RULES USED THEM CORRECTLY BUT DID NOT CAUTION YOU HOW YOU COULD GET MIXED UP WITH THOSE RULES LATER WHICH IS WHY I POINT THAT OUT.
2007-01-09 12:20:55
·
answer #1
·
answered by googooslide2000 3
·
1⤊
1⤋
Your friend is right. When you subtract a minus,
you add a plus. So +1 -(-6) = 1 + 6 = 7.
Answers to your other 2:
-24 -(-32) = -24 + 32 = 8.
+2 - (-4) = 2 + 4 = 6.
So please remember that rule!
2007-01-09 20:15:47
·
answer #2
·
answered by steiner1745 7
·
0⤊
1⤋
its 7. two negatives (the subtraction and the negative sign) make it a positive (so you are adding). If it's easier to see, it could be written also as 1+6.
same goes for the second problem: -24 + 32.
and also the third: 2 + 4.
2007-01-09 20:12:48
·
answer #3
·
answered by delicatedeluge 1
·
0⤊
1⤋
If you are getting confused, think of them in relation to hot and cold. Kind of weird, but it might help you in the beginning. Positive numbers are "hot", and negative numbers are like "cold".
So in your first example, if you have 1 hot, and you subtract 6 colds, wouldn't it get hotter? Yes it would.
So +1 - (-6)
is the same as +1 +6, which would be +7. Subtracting colds is the same as adding hots.
-24 - (-32)
You have 24 colds, and now you take away 32 of them. Well now it isn't so cold right?
-24 -(-32) is the same as saying -23+32, since taking away some cold, is the same as adding some hots.
I hope I haven't confused you, but this trick worked for my cousin!
2007-01-09 20:35:54
·
answer #4
·
answered by Wolfshadow 3
·
0⤊
1⤋
ok lol let`s start with the rule
when substruting to integers you never substruct you just add the opposit.
(+1)-(-6)=(+1)+(+6)=+7
(-24)-(-32)=(-24)+(+32)=+8
(+2)-(-4)=(+2)+(+4)=+6
always when substructing leave the first integer as it is and chang the opperation to an addition and the second integer to its opposit.
ok bye
2007-01-09 20:17:46
·
answer #5
·
answered by girls are cool and pretty 2
·
0⤊
0⤋
it's 7, two negative make a positive.
-24--32 --> -24+32=8
2 --4--> 2+4=6
2007-01-09 20:11:50
·
answer #6
·
answered by dixiebaby 2
·
0⤊
1⤋
+1 -(-6) = 1+6 = 7
-24-(-32) = -56
+2-(-4) = + 6
2007-01-09 20:11:02
·
answer #7
·
answered by NIK..! 5
·
0⤊
2⤋
an easy way to figure it...
- two positives make a positive
- two negatives make a positive
- a positive and a negative, make a negative
so in the cases of...
(+1) - (-6)= ? <-- two negatives - (-6)
1 + 6 = 7
(-24) - (-32)= ?? <-- two negatives
-24 + 32 = 8
(+2) - (-4)= -6 <-- two negatives
2 + 4 = 6
2007-01-09 20:12:32
·
answer #8
·
answered by Donny Dutch 4
·
1⤊
1⤋
(-24) - (-32) = -56
(+2) - (-4) = -2
(+1) -(-6) = -5
2007-01-09 20:11:50
·
answer #9
·
answered by Anonymous
·
1⤊
1⤋
(+1) - (-6) =
1 - - 6 =
1 + 6 = 7
2007-01-10 00:20:25
·
answer #10
·
answered by robertonereo 4
·
0⤊
1⤋